Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Des modèles nationaux (1940-1945)? - Offen, Karen (Le sièce des féminismes, 2004)
Extrait de la couverture : "Le féminisme apparaît aujourd'hui comme un événement majeur, facteur d'une révolution sociale et culturelle sans précédent du XXe siècle. Pour la première fois dans l'histoire de l'Occident, les femmes se sont émancipées de la tutelle familiale et de leur incapacité juridique, ont acquis une indépendance économique, intellectuelle et sexuelle, et se sont imposées sur la scène publique et politique. Et pourtant, en ce début du XXIe siècle, le mouvement de libération des femmes semble à un tournant. En effet, il a pris une ampleur mondiale, fait partie intégrante des grands débats de société et resurgit là où on l'attendait le moins, notamment parmi les jeunes femmes de banlieue. ... Synthèse unique d'un siècle de combats des femmes, cet ouvrage n'a pas pour but d'entrer dans la polémique mais de l'éclairer par la précision du regard historique. Il offre au public le fruit de recherches internationales encore méconnues qui, depuis trente ans, ont défriché un nouveau champ de savoir. La pluralité des combats féministes y est retracée sans complaisance : de la lutte pour le droit de vote aux combats pour la dépénalisation de l'avortement et la libération sexuelle, en passant par le droit à l'éducation et au travail."
Keywords: 1900-1999; 1940-1949; changement social; cours; discipline; droits des femmes*; fem1000; histoire; histoire des femmes*; histoire et politique; militance; premier cycle; périodes historiques; sciences humaines; thématiques

Creating emotional resonance: Interpersonal emotion work and motivational framing in a transgender community - Schrock, Douglas; Holden, Daphne; Reid, Lori (Social Problems, 2004)
In this article, we examine how interpersonal emotion work in a transgender support group and motivational framing of transgender social movement organizations together constructed favorable conditions for emotional resonance. We define emotional resonance as the emotional harmony and/or disjuncture between collective action frames and the emotional lives of potential recruits. Data derive from fieldwork, interviews, online e-mail lists and forums, community publications, activist speeches, and social movement organizations' recruitment appeals. Transgendered people joined support groups hoping to find relief from shame, fear, powerlessness, alienation, and inauthenticity. Although group members' emotion work partly accomplished such relief, it was hindered by identity conflicts and the temporal bounds of the meetings. Transgender activists and nascent social movement organizations, however, used motivational framing to promise targeted recruits a more permanent emotional resolution—one which could draw them into the movement. Our analysis moves transgender scholarship beyond issues of identity and moves framing theory beyond an almost exclusive concern with cognitive processes.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; care; identités LGBTQIA2+; militance; mouvements sociaux; personnes trans*; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; états-unis